Arsenite Binding to Sulfhydryl Groups in the Absence and Presence of Ferrihydrite: A Model Study - Hoffmann, Martin; Mikutta, Christian; Kretzschmar, Ruben (Environmental science & technology, 2014)
Binding of arsenite (As(III)) to sulfhydryl groups (Sorg(-II)) plays a key role in As detoxification mechanisms of plants and microorganisms, As remediation techniques, and reduced environmental systems rich in natural organic matter. Here, we studied the formation of Sorg(-II)–As(III) complexes on a sulfhydryl model adsorbent (Ambersep GT74 resin) in the absence and presence of ferrihydrite as a competing mineral adsorbent under reducing conditions and tested their stability against oxidation in air. Adsorption of As(III) onto the resin was studied in the pH range 4.0–9.0. On the basis of As X-ray absorption spectroscopy (XAS) results, a surface complexation model describing the pH dependence of As(III) binding to the organic adsorbent was developed. Stability constants (log K) determined for dithio ((AmbS)2AsO–) and trithio ((AmbS)3As) surface complexes were 8.4 and 7.3, respectively. The ability of sulfhydryl ligands to compete with ferrihydrite for As(III) was tested in various anoxic mixtures of both adsorbents at pH 7.0. At a 1:1 ratio of their reactive binding sites, R–SH and ≡FeOH, both adsorbents possessed nearly identical affinities for As(III). The oxidation of Sorg(-II)–As(III) complexes in water vapor saturated air over 80 days, monitored by As and S XAS, revealed that the complexed As(III) is stabilized against oxidation (t 1/2 = 318 days). Our results thus document that sulfhydryl ligands are highly competitive As(III) complexing agents that can stabilize As in its reduced oxidation state even under prolonged oxidizing conditions. These findings are particularly relevant for organic S-rich semiterrestrial environments subject to periodic redox potential changes such as peatlands, marshes, and estuaries.